Informed Molecular Design of Conjugated Oligoelectrolytes To Increase Cell Affinity and Antimicrobial Activity. (30th May 2018) - Zhou, Cheng; Chia, Geraldine W. N.; Ho, James C. S.; Seviour, Thomas; Sailov, Talgat; Liedberg, Bo; Kjelleberg, Staffan; Hinks, Jamie; Bazan, Guillermo C.
Abstract: Membrane‐intercalating conjugated oligoelectrolytes (COEs) are emerging as potential alternatives to conventional, yet increasingly ineffective, antibiotics. Three readily accessible COEs, belonging to an unreported series containing a stilbene core, namely D4, D6, and D8, were designed and synthesized so that the hydrophobicity increases with increasing side‐chain length. Decreased aqueous solubility correlates with increased uptake by E. coli . The minimum inhibitory concentration (MIC) of D8 is 4 μg mL −1 against both E. coli and E. faecalis, with an effective uptake of 72 %. In contrast, the MIC value of the shortest COE, D4, is 128 μg mL −1 owing to the low cellular uptake of 3 %. These findings demonstrate the application of rational design to generate efficacious antimicrobial COEs that have potential as low‐cost antimicrobial agents.